Evaluation of the Effect of Orally Administered Acid Suppressants On Intragastric pH in Cats. (24th December 2014) - Parkinson, S.; Tolbert, K.; Messenger, K.; Odunayo, A.; Brand, M.; Davidson, G.; Peters, E.; Reed, A.; Papich, M.G.
<x xml:space="preserve">Abstract</x> Background Acid suppressant drugs are a mainstay of treatment for cats with gastrointestinal erosion and ulceration. However, clinical studies have not been performed to compare the efficacy of commonly PO administered acid suppressants in cats. Hypothesis/Objectives To compare the effect of PO administered famotidine, fractionated omeprazole tablet (fOT), and omeprazole reformulated paste (ORP) on intragastric pH in cats. We hypothesized that both omeprazole formulations would be superior to famotidine and placebo. Animals Six healthy adult DSH colony cats. Methods Utilizing a randomized, 4‐way crossover design, cats received 0.88–1.26 mg/kg PO q12h fOT, ORP, famotidine, and placebo (lactose capsules). Intragastric pH monitoring was used to continuously record intragastric pH for 96 hours beginning on day 4 of treatment. Plasma omeprazole concentrations at steady state (day 7) were determined by high performance liquid chromatography (HPLC) with ultraviolet detection. Mean percentage time that intragastric pH was ≥3 and ≥4 were compared among groups using ANOVA with a posthoc Tukey‐Kramer test (α = 0.05). Results The mean percentage time ± SD that intragastric pH was ≥3 was 68.4 ± 35.0% for fOT, 73.9 ± 23.2% for ORP, 42.8 ± 18.6% for famotidine, and 16.0 ± 14.2% for placebo. Mean ± SD plasma omeprazole concentrations were similar in cats receiving fOT compared to those receiving ORP and in a range associated with acid suppression reported in other studies. Conclusions and Clinical Importance These results suggest that both omeprazole formulations provide superior acid suppression in cats compared to famotidine or placebo. Fractionated enteric‐coated OT is an effective acid suppressant despite disruption of the enteric coating.